1998
DOI: 10.1080/01904169809365577
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic amendments on nodulation and nitrogen fixation by cowpea

Abstract: Cornstover, garbage compost, and cowdung were added to an Alfisol (Iwo series) at the rates of 0, 23, 69, and 115 Mg ha -1 and incubated for 4 weeks in the greenhouse prior to sowing cowpea [Vigna unguiculata (L.) var. Ife Brown]. Two successive plantings were made per pot. Harvesting of the plants was at onset of flowering, 42 days after planting. Nitrogen (N) fixed was assessed using the N 2 difference method. Soil reaction (pH), organic carbon (C), and tissue N contents were increased by all the organic ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
(21 reference statements)
2
13
0
Order By: Relevance
“…High nutrient supply, especially of N, in these plots may have had a depressive effect on nodule number. Olayinka et al (1998) also observed that higher levels of applied garbage compost and cow dung depressed the number of nodules in cowpea. The proportion of total nodules: active nodules is shown in Fig.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…High nutrient supply, especially of N, in these plots may have had a depressive effect on nodule number. Olayinka et al (1998) also observed that higher levels of applied garbage compost and cow dung depressed the number of nodules in cowpea. The proportion of total nodules: active nodules is shown in Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Hence, in contrast to the finding that the number of rhizobium was not significantly affected by organic modifications ( Danso and Alexander 1974), rhizobium was found to benefit from the addition to the soil of small amounts of manure ( Adebayo 1985). Also, Olayinka et al (1998) found that organic modifications would benefit N 2 fixation in soils low in indigenous organic matter. An adequate supply of mineral nutrients to legumes enhances N 2 fixation.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of cow dung, poultry droppings, refuse compost and farmyard manure as suitable soil amendments in the tropics has been reported [1,2,3,4]. Application of organic materials as fertilizers provides growthregulating substances and improves the physical, chemical and microbial properties of the soil [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Reijnties et al (1992) and Adepetu (1997) remarked that the downward trend in food production should prompt farmers to amend the soil with different materials in order to enhance growth and yield of crops. Several organic materials such as cattle dung, poultry dropping, pig dung and refuse compost have been recommended to subsistence farmers in West Africa as soil amendments for increasing crop yield (Sobulo & Babalola, 1992;Ismail et al, 1999;Olayinka, 1996;Olayinka et al, 1998). Zougmore et al (2006) reported that poultry dropping and cattle dung increased root growth of maize and the crop extracted soil water more efficiently for increased grain yield.…”
Section: Introductionmentioning
confidence: 99%